A Learner-Centered Approach to Learning: Students from Diverse Professional Backgrounds - Ghafar, Zanyar Nathir (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
The review paper aims to focus on the learner-centered approach to education, which is characterized by student participation and a focus on tailoring instructional methodologies to accommodate each student's circumstances, interests, and goals. For this review research, secondary materials, which include projects, theories, and articles that have previously been published, were used.  The study results from increased student engagement, improved learning outcomes, and the development of lifelong learning skills. Nevertheless, there are potential challenges that may arise, including the need for teacher instruction and assistance, the potential for inconsistent student involvement, and the imperative for meticulous planning and readiness. Technological improvements have facilitated students' access to a plethora of educational materials, enhanced their ability to collaborate, and provided them with the opportunity to receive tailored and customizable teachings. The research findings demonstrated that promoting collaboration among students from various professional backgrounds via team-based work is an additional method of incorporating interprofessional education. Simulations and other interactive instructional methods, together with student involvement in patient care and decision-making, may be beneficial in a clinical environment.